“LOVE” AS A SEMANTIC GROUP OF “SPIRITUALITY” SEMANTIC FIELD - Barotova Saodat Uktamovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
The presented article is devoted to the analysis of “Love” as a semantic group of “spirituality” semantic field. The fact that the essence of the language is two-sided, that each of the formal and substantive aspects of the language has its own internal structure, that each is an internal system consisting of its parts, and that the relationship between them makes the language work is not only recognized by everyone. Linguistic level, led to the emergence of the concept, but also to its use in a very broad sense. Language units can be combined on the basis of various symbols. The main feature of dividing the language into levels is the characteristic of hierarchical level of linguistic units, and the relationship of relatively identical units that do not have a hierarchical relationship with each other can be understood as a linguistic level. has a stepwise relationship with l unit. In this case, the lower-level unit is formed from the higher-level unit, that is, it has the property of being part of the higher-level unit. Language is viewed as a single hierarchically formed system, and such an approach to the internal structure of language is a composite concept. Homogeneous and heterogeneous relationships are distinguished in the step-by-step relationship of events. In a homogeneous relationship, one of the units is considered as a model, standard for others.